Immunization Status, Parenting Style, and Posyandu Activeness on Wasting Incidents in Toddlers - Isabella, Nicky Clarisa Anggia; Marsanti, Avicena Sakufa; Wibowo, Pipid Ari (Jurnal Ilmiah Kesehatan (JIKA), 2024)
In 2020 there were 15 cases of wasting (1,5%), in there were 41 cases of wasting (4,9%) and in 2022 there were 46 cases of wasting (5,4%) at the Kesugihan Health Center. Therefore the purpose of this study was to analyze the influence of immunization status, parenting style and Posyandu activity on wasting in toddlers in the Work Area of ??the Pulung District Kesugihan Health Center, Ponorogo Regency. This study used an observational analytic method with a case control approach. The population in this research was 54, while the subjects were 27 case subjects and 27 controls using a purposive sampling method. Furthermore, the data collected will be analyzed using univariate, bivariate analysis with chi-square test and multivariate analysis using logistic regression. The results of the bivariate analysis showed that the variables of posyandu activity and mother's parenting style had a relationship with wasting in toddlers. Meanwhile, the immunization status variable has no relationship with the incidence of wasting in toddlers. Meanwhile, based on the results of the multivariate analysis research, it shows that the variables of Posyandu activity and parenting patterns have an influence on the incidence of wasting in toddlers.